TRENDS IN THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE- BASED TECHNOLOGY IN EDUCATION - Loso Judijanto; M. Rifqi Atsani; Siti Chadijah (Adisam Publisher, 2024)
Artificial intelligence in education has grown to be a prominent trend. AI has a lot of promise, particularly for improving learning's efficacy and efficiency. Artificial intelligence is one technology advancement that has the power to drastically change the way that we teach and learn. AI offers a number of benefits and exciting new opportunities in the realm of education. One of the main benefits of using AI in education is the capacity to adapt training. Through data analysis and intelligent algorithm modeling, AI systems can understand each individual's unique preferences, needs and learning styles. This allows teachers to present learning material tailored to students' level of understanding more effectively. With the use of artificial intelligence, education may be tailored to each student's interests, learning style, and speed. AI is able to thoroughly examine student learning data, pinpoint strengths and shortcomings, and offer pertinent learning suggestions. In this study, the research strategy used was a review of the literature. This study explores the use of artificial intelligence technology in education, including how it can create new learning possibilities, how it affects the learning process, and how it will shape education going forward.